The Peculiarities of Manifesting Inducement and Imperation in English (Bulletin of Yerevan University B: Philology, 2021)
The article introduces the means of expressing imperation and inducement in English as well as the possibilities of their differentiation, similarities and semantic divergences. Some characteristic definitions are also presented, due to which it becomes possible to distinguish imperative and inductive sentences distinctly.
Keywords: imperative, inducement, strong imperative, weak imperative, softened imperative, direct imperative, indirect imperative, positive imperative, negative imperative, ethical imperative